Effects of different brain surveillance strategies on outcomes for patients with EGFR-mutant metastatic lung adenocarcinoma under targeted therapy. (December 2019) - Shen, Chia-I; Huang, Hsu-Ching; Chiang, Chi-Lu; Luo, Yung-Hung; Shiao, Tsu-Hui; Chiu, Chao-Hua
Highlights: Though regular brain MRI detected metastasis earlier, overall survival was similar. Time to EGFR-TKI treatment failure was similar. No difference in the intracranial failure patterns and cause. Abstract: Objectives: Brain metastasis (BM) is common in patients with epidermal growth factor receptor (EGFR)-mutant lung cancer. However, the brain surveillance strategy during treatment in advanced lung cancer patients varies, and the impact on clinical outcome is unclear. Here we aimed to evaluate the effect of different brain surveillance strategies on the clinical characteristics and treatment outcome in patients with EGFR-mutant lung adenocarcinoma treated with first-line EGFR tyrosine kinase inhibitors (EGFR-TKIs). Materials and methods: This is a retrospective observational study conducted in a medical center in an area with high prevalence of EGFR mutation. Patients with initially diagnosed stage IV EGFR-mutant lung adenocarcinoma were included. Patients undergoing regular brain magnetic resonance imaging (MRI) every 3-6 months were categorized in the regular follow-up (RFU) group, and the rest were categorized in the liberal follow-up (LFU) group. Clinical outcomes were collected and analyzed. Results: A total of 310 patients were included, and 43.5% initially had brain metastases. Patients in the LFU group were significantly older than those in the RFU group (median age: 67 vs 62, p < 0.001). The overall survival and time-to-treatment failure of patients with initial EGFR-TKIs treatment showed no statistical difference between the two groups. However, the intracranial progression free survival was significantly shorter in the RFU group than in the LFU group (p = 0.009). The risk of mortality was similar in the LFU and RFU groups. There was no difference in the intracranial progression patterns and cause of death between the two groups. Conclusions: For EGFR-mutant lung adenocarcinoma patients who used EGFR-TKIs as the frontline therapy, regular or liberal brain MRI follow-up showed no significant impact on the outcome, irrespective of initial brain metastasis.